Nitrogen dioxide is genotoxic in urban concentrations. (May 2013) - Koehler, Christian; Thielen, Sebastian; Ginzkey, Christian; Hackenberg, Stephan; Scherzed, Agmal; Burghartz, Marc; Paulus, Michael; Hagen, Rudolf; Kleinsasser, Norbert Helmut
Abstract In the discussion on toxic and genotoxic thresholds of air pollutants such as nitrogen dioxide (NO2), realistically low urban concentration ranges are of major interest. For NO2, the WHO defines the annual limit value as corresponding to 0.02 ppm. In the present study, the toxicity and genotoxicity of NO2 is set at a concentration under this limit value and examined in human nasal epithelium at different exposure durations in vitro. Nasal epithelial mucosa samples of 10 donors were harvested during nasal air passage surgery and cultured as an air–liquid interface. Exposure to 0.01 ppm NO2 or synthetic air as a control was performed for 0.5, 1, 2 and 3 h. Analysis included the caspase-3 ELISA, the single cell microgel electrophoresis (comet) assay and the micronucleus assay. The caspase-3 activity was not influenced by NO2 exposure, DNA strand fragmentation correlated with exposure durations to NO2 at 0.01 ppm NO2, and no cytotoxic effects such as apoptosis, necrosis or disturbances of cell proliferation were present. However, micronucleus induction as a sign of genotoxicity at an exposure duration of 3 h could be shown. Shorter exposures did not induce micronucleus formation. In summary, genotoxicity of NO2 could be demonstrated at a common urban concentration in vitro, but a threshold of NO2 genotoxicity could not be defined based on the present experiments.